CAMPUR KODE DAN ALIH KODE PADA PEMBELAJARAN BASIC ENGLISH BAGI MAHASISWA/I DI LABUAN BAJO - Katarina Noviming Sakura (Prima Magistra: Jurnal Ilmiah Kependidikan, 2023)
This research aims to describe the application of code-mixing and code-switching as one of English learning methods in Politeknik eLBajo Commodus, particularly in Basic English Class. The method of this research is field observation during the time of Basic English. Several example speeches which contain code-mixing and code-switching during the class are used as the data. The data is then analyzed by the theory to find out the contexts and types of code-mixing and code-switching that happened in the Basic English Class. The result shows that code-mixing is used in some contexts, such as in welcome greeting, small talk before the class starts, to open the lecture, while giving the lecture, and interact with each other in the class. All those are outer code-mixing. As for code-switching, there are situational and metaphoris code-switching, and both in insertion and alternation. The code-switching is used when the students still use bahasa Indonesia more often. When there are students that do not understand the questions, and as a translation from bahasa Indonesia, if needed, code-switching is applied. This research shows that the code-mixing and code-switching can be used as English teaching method and the lecturer must control the use itself so that English is still being the main language in the English class.